Impactos da revista agitação na visibilidade do CIEE : imagens e imaginários sociais - Avanzi, Renato (2008)
This research analyzes the communicational impacts and symbolic effects of Agitação Magazine (Revista Agitação), the most important house organ of the largest nongovernmental organization of the third sector in Brazil: CIEE (Integration Center between Companies and Universities). The main research questions are: a) what are the impacts of Agitação in the building of visibility, credibility maintenance and institutional mark consolidation aimed by CIEE; b) what are the relations observed between the imagetic signs on the magazine covers and the values proposed by CIEE; c) what social imaginaries are being built and /or reiterated when we analyze this imagetic discourse; d) how the main segments of the readers – executives, educators, representatives of the public power, and students – apprehend and interpret the communicative intention of the Magazine, considering the different aspects of its mediational function; and e) what is the visibility effectively obtained by CIEE through this practice of cultural consumption. To answer to these questions, some analytical resources are adopted: in a first moment (chapter 3), the context data and a general view to locate CIEE in the social-cultural macro scenarios are presented, using them to punctuate the main steps for the consolidation of the organizational communication policy. In a second moment (chapter 4), one of the main communication vehicles between the organization and its target publics is investigated, prioritizing the way imagetic elements and the social-imaginary – about work, success, empregability, among others – are articulated on the covers of Agitação Magazine – reiterated by CIEE’s discoursive practices. In a third moment (chapter 5), the impacts of the magazine on students (one of the target publics) will be analyzed through their narratives. Still on chapter 5, a comparative analysis articulates the results obtained in each step: CIEE’s discoursive practices, Agitação’s imagetic analysis and the reader’s narratives. In order to finish this research (chapter 6), the final considerations bring a summary of all the conclusions obtained in each of the previous chapters. This way, the research uses multi methodological tools: documental research, bibliographical investigation, imagetic analysis and focus groups for a qualitative study. Besides, it considers the adoption of a clear communication strategy as a fundamental mark in the consolidation of the major institutional visibility.